Pengaruh Edukasi Farmasis terhadap Outcome Terapi Pasien TB Paru Fase Intensif di RSUP Persahabatan Periode Maret-Juli 2015 - Reza Agung Sriwijaya; Shirly Kumala; Sesilia A. Keban (Jurnal Penelitian Sains, 2018)
The background knowledge of this research is based on the amount of patients’ pulmonary tubercu-losis who get failed doing their therapy and recur in having it after doing the treatment at RSUP Persahaba-tan.The objective of this research is to decrease the amount of patients get failed doing the therapy and recur at RSUP Persahabatan. The method of the research is Quasi-experimental with Nonrandomized Control Group Pretest-Postest Design. Furthermore, the technical sampling used is voluntaryby two apparent groups, 54 pa-tients as control group and 54 patients as experiment group.The instrument of this research are pre-test,posttest and Likert Questionair Model which is used to measure the knowledge and compliance toward the outcome of the therapy before and after it meets a good validity and reability test with standard α = 0,05. The conclusion is education pharmacy can increase knowledge and compliance with TB patients so that the outcomes of therapy against Pulmonary TB patients at RSUP Persahabatan is improved.